Aquaporins in sepsis- an update - Rump, Katharina; Adamzik, Michael (Frontiers in Immunology, 2024)
Aquaporins (AQPs), a family of membrane proteins that facilitate the transport of water and small solutes, have garnered increasing attention for their role in sepsis, not only in fluid balance but also in immune modulation and metabolic regulation. Sepsis, characterized by an excessive and dysregulated immune response to infection, leads to widespread organ dysfunction and significant mortality. This review focuses on the emerging roles of aquaporins in immune metabolism and their potential as therapeutic targets in sepsis, with particular attention to the modulation of inflammatory responses and organ protection. Additionally, it explores the diverse roles of aquaporins across various organ systems, highlighting their contributions to renal function, pulmonary gas exchange, cardiac protection, and gastrointestinal barrier integrity in the context of sepsis. Recent studies suggest that AQPs, particularly aquaglyceroporins like AQP3, AQP7, AQP9, and AQP10, play pivotal roles in immune cell metabolism and offer new therapeutic avenues for sepsis treatment. In the context of sepsis, immune cells undergo metabolic shifts to meet the heightened energy demands of the inflammatory response. A key adaptation is the shift from oxidative phosphorylation (OXPHOS) to aerobic glycolysis, where pyruvate is converted to lactate, enabling faster ATP production. AQPs, particularly aquaglyceroporins, may facilitate this process by transporting glycerol, a substrate that fuels glycolysis. AQP3, for example, enhances glucose metabolism by transporting glycerol and complementing glucose uptake via GLUT1, while also regulating O-GlcNAcylation, a post-translational modification that boosts glycolytic flux. AQP7 could further contributes to immune cell energy production by influencing lipid metabolism and promoting glycolysis through p38 signaling. These mechanisms could be crucial for maintaining the energy supply needed for an effective immune response during sepsis. Beyond metabolism, AQPs also regulate key immune functions. AQP9, highly expressed in septic patients, is essential for neutrophil migration and activation, both of which are critical for controlling infection. AQP3, on the other hand, modulates inflammation through the Toll-like receptor 4 (TLR4) pathway, while AQP1 plays a role in immune responses by activating the PI3K pathway, promoting macrophage polarization, and protecting against lipopolysaccharide (LPS)-induced acute kidney injury (AKI). These insights into the immunoregulatory roles of AQPs suggest their potential as therapeutic targets to modulate inflammation in sepsis. Therapeutically, AQPs present promising targets for reducing organ damage and improving survival in sepsis. For instance, inhibition of AQP9 with compounds like HTS13286 or RG100204 has been shown to reduce inflammation and improve survival by modulating NF-κB signaling and decreasing oxidative stress in animal models. AQP5 inhibition with methazolamide and furosemide has demonstrated efficacy in reducing immune cell migration and lung injury, suggesting its potential in treating acute lung injury (ALI) in sepsis. Additionally, the regulation of AQP1 through non-coding RNAs (lncRNAs and miRNAs) may offer new strategies to mitigate organ damage and inflammatory responses. Moreover, AQPs have emerged as potential biomarkers for sepsis progression and outcomes. Altered expression of AQPs, such as AQP1, AQP3, and AQP5, correlates with sepsis severity, and polymorphisms in AQP5 have been linked to better survival rates and improved outcomes in sepsis-related acute respiratory distress syndrome (ARDS). This suggests that AQP expression could be used to stratify patients and tailor treatments based on individual AQP profiles. In conclusion, AQPs play a multifaceted role in the pathophysiology of sepsis, extending beyond fluid balance to crucial involvement in immune metabolism and inflammation. Targeting AQPs offers novel therapeutic strategies to mitigate sepsis-induced organ damage and improve patient survival. Continued research into the metabolic and immune functions of AQPs will be essential for developing targeted therapies that can be translated into clinical practice.